Evaluation Of Tamarind (Tamarindus Indica L) Shell Tannin Extracts As A Corrosion Inhibitor Of Mild Steel In Acidic Medium - Abdulmajid, Abdullahi (2020)
The aim of this research was to study how eco-friendly corrosion inhibitors for acidic media systems could be advanced and used through evaluation of tamarind shell tannin extracts (TSTE) isolated using methanol (TME), 70% acetone (TAE), water (TWE), and ethyl acetate (TEAE).